Differentiating between a silicone oil bubble and a dislocated intraocular lens - Shipman, K; Patel, C (2009)
This article aims to demonstrate how a silicone oil bubble can be mistaken for a dislocated intraocular lens. An 80-year-old gentleman was referred by his optometrist with the diagnosis of dislocated IOL in a pseudophakic eye. Eye examination revealed a silicone oil bubble from previous retinal-detachment surgery and that the lens was in-situ. In conclusion, a history of retinal detachment surgery should alert one that an oil bubble can be misinterpreted as a dislocated IOL. © 2009 Spanish Council of Optometry.